The South Texas Health Status Review : A Health Disparities Roadmap. - Ramirez, Amelie G.; Thompson, Ian M.; Vela, Leonel (Cham : Springer International Publishing AG, 2013)
This book is a roadmap of the disparities that burden the health of South Texas residents, especially Hispanics, compared to the rest of Texas and nation. Surveys more than 35 health indicators from cancers to diabetes to HIV/AIDS to maternal health and more.
Health Conditions with Higher Rates in South Texas -- Recommendations -- References -- Appendix A: Data Sources -- BRFSS Health Indicator Prevalence Definitions -- PRAMS Health Indicator Prevalence Definitions -- Appendix B: Data Analysis Methods -- Appendix C: South Texas County Demographics, 2010 -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books